Pembelajaran Menulis Teks Fabel yang Berorientasi pada Keterampilan Berpikir Kreatif dengan Model Moody Berbantuan Aplikasi Powtoon pada Peserta Didik Kelas VII SMPN 35 Bandung - Dila Ardika; Dheni Harmaen; Rendy Triandy (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This research is based on the selection of models and media that are less creative and innovative in learning to write fable texts so that students feel bored and find it difficult to write. The purpose of this study is to test the effectiveness of learning to write fable text with the moody model assisted by the powtoon application for VII grade students of SMPN 35 Bandung. This research uses a quasi-experimental quantitative method and a true experimental pretest-posttest control group design, and the research subjects consist of 2 classes. The results of the research show 1) the author was able to plan and implement learning to write fable texts, as evidenced by the scores obtained at 3.55 and 3.54 in the very good category, 2) the students' abilities before receiving treatment had not yet reached the criteria for achieving Learning Objectives (KKTP) with The total average obtained was 57.15, 3) the students' abilities after receiving treatment using the Moody model assisted by the Powtoon application experienced a significant increase as evidenced by the Wilcoxon test results showing the Asymp value. Sig. (2-tailed) < 0.05, 4) the moody model assisted by the powtoon application is effectively used in learning to write fable texts as proven by the achievement of the Maan Whitney test score showing the Asymp value. Sig (2 tailed) is 0.00, < 0.05, which means that the moody model assisted by the powtoon application is more effective in use compared to the control class.